From desert dust to ongoing soil formation in the mountainous areas of the south Levant - Sandler, Amir; Zaid, Mahmoud; Stein, Mordechai (Catena, 2023)
Mediterranean soils of the south Levant have been investigated and described during the past several decades, especially brown-reddish mountain soils, but certain issues, such as the role of desert dust as a parent material, remain unresolved. This study aims to quantify the role of desert dust in the formation of the mountain soils of the south Levant area, examine the environmental factors that affect the soil formation processes, and evaluate their time of formation. This is done by sampling and analyzing soil sites along two west-east transects across the Judea and Samaria mountains that encompass the transition from the Mediterranean to the semiarid climate. The new database includes the bulk mineralogical and chemical compositions of major oxides and trace elements, particle size distributions, and basic soil's parameters. Although the range of calcite content in the soils studied is large (>1 % to 60 %), all soil types have similar grain size distributions of three modes: 45–55 μm mode within the coarse silt fraction, 20–25 μm mode within the fine silt fraction, and a clay mode. Local (Jerusalem) dust, collected near the sampled soils, is distinguished from desert dust by a lower quartz content and lower concentrations of SiO2, TiO2, Th, and Zr, suggesting that the local dust is a mixture of remote desert dust and local sources. The soils on the eastern side of the Judean Mountains, under a semiarid climate, are dominated by the coarse silt mode, and their compositions reflect a higher contribution of desert dust and weaker pedogenic processes. The pedogenic formation of smectites turns the clay fraction into the main grain size mode in the leached soils of the western side, under higher precipitation and denser vegetation. The almost identical compositions found for two adjacent soils on limestone and on chert demonstrate that dust is almost the exclusive parent material for soils presently forming on hard sedimentary rocks. This, other chemical parameters, and additional field observations indicate no relation between soils and bedrock or visible karstic activity at present. Accordingly, soil formation in the mountainous areas of the south Levant is a result of ongoing dust accumulation and transformation since the last major erosion event in the early Holocene.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Cambisols; Chemical composition; Desert dust; Judea and Samaria mountains; Mediterranean soils; Mineralogical composition; REE; Rendzina; South Levant; Terra rossa